Village Baseline Study: Site Analysis Report for Haryana - Karnal, India - Shrestha, K.; Singh, R.; Upraity, Varsha; Acharya, Ganesh; Rayamajhi, Arati; Nagrale, B; Kumar, S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This is the report of the village baseline study of Pakhana in the CCAFS benchmark site of Karnal, India conducted from March 15-17, 2013 to complement an earlier household baseline survey done in the same village. Pakhana is located in the fertile flat land of the Indo-Gangetic plains and has good access to roads, markets, electricity and communication. The community has not experienced a food crisis and 90% of the population enjoys year-round food security. Pakhana benefited from the Green Revolution and has adopted improved varieties and the use of chemical fertilizers and pesticides. However, Pakhana now faces challenges resulting from population growth, deforestation, reduced and variable rainfall, declining soil fertility and organic matter, monocropping, over application of chemical inputs, and depletion of the water table. As a result, access to water resources is more difficult, profits have decreased and production is constrained. Without adjustments, Pakhana’s food security, livelihoods and natural resources will be further strained and threatened.